The Civilizational Aspects Of The Levant Through The Book Of Countries To Ibn Al-faqih - WISHAH, Ghassan Mahmoud (جامعة الوادي - University of Eloued, 2020)
IBN AL-faqih Al-Baladin book considers one of the most important sources which contained important civilizational information about the Levant , Ibn alFaqih drew a completed picture about the civil of levant , the research contained a lot of important points: The first: Ibn al-Faqih definition and his method in preparing the book. The second : The benifets of the Levant from al-Baldin book. The third :the civilizational sides in the levant from alBaldin book , then , the results and list of important sources and references.
مقال
Keywords: Civilization,Sham,In al – Faith, Book Countries